Cistanche tubulosa glycosides ameliorate cognitive decline in APP/PS1 mice via modulation of gut microbiota and fatty acid metabolism: insights from multi-omics and experimental validation - Hou, Rui; Song, Wei; Nan, Yi; Gong, Yiyi; Liu, Jieying; Liu, Jialin (Frontiers in Pharmacology, 2025)
ObjectiveThe dried succulent stem of C. tubulosa (Schenk) Wight has long been used as herbal medicine in China and other regions of Asia for its tonifying properties. This study aimed to elucidate the pharmacological mechanisms of the total glycosides from Cistanche tubulosa (GCT) in ameliorating cognitive decline, with a focus on gut microbiota remodeling and metabolic regulation.MethodsSix-month-old APP/PS1 double-transgenic mice received oral GCT at three doses or donepezil for 60 days. Cognitive function was assessed by the Morris water maze. Aβ burden and inflammatory factors were evaluated by immunohistochemistry and ELISA. Gut microbiota was analyzed using 16S rRNA sequencing. Metabolomic profiles of mice serum and brain were profiled by a targeted metabolomics approach that enabled simultaneous quantitation of 306 metabolites. The effect of GCT on pure-cultured bacterial strain was assessed via growth curve analysis in vitro.ResultsGCT treatment significantly improved spatial memory and reduced the protein levels of Aβ and proinflammatory factors in APP/PS1 mice. Multi-omics analyses revealed that GCT rapidly enriched beneficial taxa like Akkermansia and suppresses Firmicutes since the seventh day of intervention, leading to increased neuroprotective short-chain fatty acids (e.g., β-hydroxybutyrate) and decreased pro-inflammatory long-chain fatty acids in both serum and brain. Crucially, in-vitro experiments demonstrated that GCT directly promoted the proliferation of Akkermansia muciniphila, a key probiotic implicated in AD amelioration.ConclusionThis work uncovers a novel “gut microbiota-fatty acid metabolism-neuroinflammation” axis as the primary mechanism underlying GCT’s anti-AD effects. These findings highlight GCT’s therapeutic potential and offer new mechanistic insights into how low-bioavailability phytochemicals exert systemic benefits via the gut-brain axis.